DEVELOPING A HOLISTIC MUSLIM CHARACTER THROUGH MORALITY TOWARD ALLAH, THE PROPHET, PARANETS, AND THE SELF - Fitria Muthmainnah; Jihan Khairum Nisa (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
the practice of morality toward Allah SWT, the Prophet Muhammad SAW, parents, and the self. Morality in Islam encompasses not only the vertical relationship with the Creator and His Messenger but also the horizontal relationship with fellow human beings and oneself. This research employs a qualitative method with a literature review approach, analyzing sources from the Qur’an, Hadith, and relevant academic studies. The findings indicate that integrating morality toward Allah and the Prophet serves as the fundamental foundation in shaping a strong character, while morality toward parents and oneself reinforces the social and psychological dimensions of a Muslim individual. Consistent application of these moral values contributes to the formation of a harmonious, responsible, and virtuous Muslim personality in daily life. This study offers significant implications for Islamic character education and spiritual development of the Muslim community